Effects of pidotimod and bifidobacteria mixture on clinical symptoms and urinary metabolomic profile of children with recurrent respiratory infections: a randomized placebo-controlled trial. (October 2019) - Santamaria, Francesca; Montella, Silvia; Stocchero, Matteo; Pirillo, Paola; Bozzetto, Sara; Giordano, Giuseppe; Poeta, Marco; Baraldi, Eugenio
Abstract: Background: Many preschool children develop recurrent respiratory tract infections (RRI). Strategies to prevent RRI include the use of immunomodulators as pidotimod or probiotics, but there is limited evidence of their efficacy on clinical features or on urine metabolic profile. Objective: To evaluate whether pidotimod and/or bifidobacteria can reduce RRI morbidity and influence the urine metabolic profile in preschool children. Materials and methods: Children aged 3–6 years with RRI were enrolled in a four-arm, exploratory, prospective, randomized, double-blinded, placebo-controlled trial. Patients were randomly assigned to receive pidotimod plus bifidobacteria, pidotimod plus placebo, bifidobacteria plus placebo or double placebo for the first 10 days of each month over 4 consecutive months. Respiratory symptoms and infections were recorded with a daily diary by parents during the study. Metabolomic analyses on urine samples collected before and after treatment were performed. Results: Compared to placebo, children receiving pidotimod, alone or with bifidobacteria, had more symptom-free days (69 versus 44, p = 0.003; and 65 versus 44, p = 0.02, respectively) and a lower percentage of days with common cold (17% versus 37%, p = 0.005; and 15% versus 37%, p = 0.004, respectively). The metabolomic analysis showed that children treated with Pidotimod (alone or in combination with bifidobacteria) present, respect to children treated with placebo, a biochemical profile characterized by compounds related to the pathway of steroids hormones, hippuric acid and tryptophan. No significant difference in the metabolic profile was found between children receiving bifidobacteria alone and controls. Conclusions: Preschool children with RRI treated with pidotimod have better clinical outcomes and a different urine metabolomic profile than subjects receiving placebo. Further investigations are needed to clarify the connection between pidotimod and gut microbiome. Graphical abstract: Image 1